Macrokinetic effects in perhydro-N-ethylcarbazole dehydrogenation and H2 productivity optimization by using egg-shell catalysts. Issue 10 (21st August 2015) - Peters, Willi; Seidel, Alexander; Herzog, Stefan; Bösmann, Andreas; Schwieger, Wilhelm; Wasserscheid, Peter
Abstract : This contribution deals with pore diffusion influences on the dehydrogenation kinetics of perhydro- N -ethylcarbazole (H12-NEC). Abstract : This contribution deals with pore diffusion influences on the dehydrogenation kinetics of perhydro- N -ethylcarbazole (H12-NEC). The reaction is of high interest in the context of hydrogen storage in the N -ethylcarbazole (NEC)/perhydro- N -ethylcarbazole (H12-NEC) Liquid Organic Hydrogen Carrier (LOHC) system. The hydrogen content of H12-NEC is 5.8 wt% and total dehydrogenation releases for each mL of H12-NEC more than 600 mL of H2 . Further optimization of H12-NEC dehydrogenation catalysis requires a better understanding of the role of mass transfer effects. Pore diffusion effects have been studied by preparing egg-shell catalysts (Pt/γ-alumina layer on α-alumina core) of different active layer thicknesses (24 –88 μm). It has been found that even at very thin catalyst layers (24 μm) the kinetic regime is limited to 235 °C, thus pore diffusion effects the dehydrogenation in almost all commercial catalysts strongly.